Simple Model for Simulating Characteristics of River Flow Velocity in Large Scale - Husin Alatas; Dyo D. Prayuda; Achmad Syafiuddin; May Parlindungan; Nurjaman O. Suhendra; Hidayat Pawitan (International Journal of Geophysics)
We propose a simple computer based phenomenological model to simulate the characteristics of river flow velocity in large scale. We use shuttle radar tomography mission based digital elevation model in grid form to define the terrain of catchment area. The model relies on mass-momentum conservation law and modified equation of motion of falling body in inclined plane. We assume inelastic collision occurs at every junction of two river branches to describe the dynamics of merged flow velocity.